Penelusuran Bakat Olahraga Anak Usia Dini di Sekolah Dasar (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2016)
Purpose of this study to know who owned sporting talent early childhood in State ElementarySchools in Cepu Blora Academic Year 2015? Data collection technique used (1) the documentationused to obtain data about the names of members of the population who took the testsport search and photo test execution sport search, (2) questionnaire was used to determinethe extent of the role of the teacher penjasorkes related to coaching and talent developmentparticipants students, (3) aptitude tests are used to determine the student sport giftedness. Theresult showed that the Search Talent Sports Childhood In public elementary school in CepuBlora academic Year 2015 is 33% (38 of 115 children) talented in sports sprint, 13% (15 of115 children) talented in sports high jump , 16% (18 of 115 children) talented in sports longjump, 14% (16 of 115 children) talented at the sport of distance running, 11% (13 of 115children) talented in gymnastics, 9% (10 of 115 children ) talented in the sport of table tennis,4% (5 out of 115 children) talented in sports weightlifting. Based on the results of the researchcan be concluded that the public elementary school students in Cepu potentials or talents in thefield of sport based on test results sport scouting talent search conducted.